Restaurant Recommendation Decision Support System Using Topsis System - Rogawati, Nesya; Susilawati, Indah; Witanti, Arita (Universitas Al Azhar Indonesia, 2023)
The vast technology development in the culinary aspect makes all kinds of information could be acquired easily. Information is needed to be one of some considerations when a person is going to book a seat in a restaurant. Hungryhub is restaurant booking service provider which helps customers to be able to make a reservation online. This research background is Hungryhub website development innovation which offers so many restaurants. The aim of this research is to help customers upon making decisions with restaurants' recommended option alternatives.This research is using Technique for Other Reference by Similarity to Idea Solution (Topsis). Data is collected from documentation and interviews. The documentation is obtained from survey fulfillment by the users which would be processed and references of the restaurant recommendations for the users themselves. The interviews are done with the Hungryhub operational team to get the restaurants' data which have cooperated with Hungryhub. The topsis method is chosen because it has a concept that chosen alternatives are alternatives which have the shortest range to the ideal positive solutions and have the farthest range to the ideal negative solutions. The result of this research is a recommendation system which could display alternative restaurants' ranking result.